1999
DOI: 10.1097/00001756-199903170-00011
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces amyloid-like aggregate formation of NACP/α-synuclein in vitro

Abstract: The precursor of non-amyloid beta protein component of Alzheimer's disease amyloid (NACP/alpha-synuclein), found in Lewy bodies of Parkinson's disease (PD), is a presynaptic protein genetically linked to some familial types PD. Mechanisms of abnormal NACP/alpha-synuclein aggregation in neurodegenerative diseases are unclear. Since oxidative stress might play a role in PD pathogenesis, we investigated the role of iron and peroxide in NACP/alpha-synuclein aggregation. Immunoblot analysis showed that human NACP/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
242
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 416 publications
(248 citation statements)
references
References 5 publications
5
242
1
Order By: Relevance
“…The incremental aggregation process of ␣-synuclein involves several modifications (misfolding, dimer and oligomer formation, and self-aggregation) and is linked to Parkinson's disease-associated mutations (5,22,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). In this study, we detected abnormal ␣-synuclein species based on their detergent solubility and electrophoretic mobility characteristics in three different systems: human DLB cortex, transgenic mice overexpressing wild type human ␣-synuclein, and a transiently transfected cell culture system.…”
Section: Discussionmentioning
confidence: 95%
“…The incremental aggregation process of ␣-synuclein involves several modifications (misfolding, dimer and oligomer formation, and self-aggregation) and is linked to Parkinson's disease-associated mutations (5,22,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). In this study, we detected abnormal ␣-synuclein species based on their detergent solubility and electrophoretic mobility characteristics in three different systems: human DLB cortex, transgenic mice overexpressing wild type human ␣-synuclein, and a transiently transfected cell culture system.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence of excessive oxidation is found in the brains of PD patients (106-108). Hashimoto et al (109) demonstrated that treatment of ␣-SYN with H 2 O 2 and ferrous iron in solution led to the formation of insoluble aggregates of ␣-SYN. Treatment of neuroblastoma cells engineered to overexpress A53T, A30P, and WT ␣-SYN with iron resulted in the formation of ␣-SYN aggregates, and the mutants were more susceptible (110).…”
Section: Concentrationmentioning
confidence: 99%
“…Other possible mechanisms of iron toxicity are impaired production of metalloproteins, altered expression of proteins containing the regulatory iron responsive element (IRE) on their RNA [2], activation of microglial cells leading to inflammation [25], promotion of protein misfolding and aggregation [26][27][28] and triggering cell death by the novel iron-dependent pathway termed 'ferroptosis' [29][30][31]. Even though these processes were convincingly demonstrated in vitro and in animal studies, there is currently little direct evidence that they are causally involved in neurodegenerative processes as it occurs in humans.…”
Section: Causes and Consequences Of Cerebral Iron Accumulationmentioning
confidence: 99%